Preparation method of superhard and tough self-lubricating TiAlSiCN coating
By preparing super-hard and tough self-lubricating TiAlSiCN nanocomposite coating on fuel cell metal bipolar plates, the problems of carbon-based coating cracking and hydrogen element residues are solved, and the conductivity and corrosion resistance of the bipolar plates are improved. The efficient stability and safety of fuel cells are achieved.
Patent Information
- Application Number
- CN202411252311.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The carbon-based coating of metal bipolar plates in fuel cells is prone to cracking and falling off during use, resulting in a shortening of life. The existing magnetron sputtering technology has the problem of residual hydrogen element, which affects the conductive and corrosion resistance of the coating.
Ultra-hard and tough self-lubricated TiAlSiCN nanocomposite coating is prepared on tungsten steel, stainless steel, copper alloy and other substrates using Ti70Al20Si10, Ti or Ti50Al50, C targets. Specific micro-pulse can be set by using high-power pulse magnetron sputtering technology. Parameters and air pressure conditions, prepare a 2-10 μm thickness TiAlSiCN coating, including a metal binding force layer and a nitride gradient layer, ensuring the high hardness and toughness of the coating.
The preparation of high hardness and toughness coatings is achieved, the conductivity and corrosion resistance of metal bipolar plates are improved, the hydrogen carbon content is reduced, the efficiency and stability of fuel cells are enhanced, and the use of acetylene gas is safer and more reliable.
Smart Images

Figure CN119121159A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon-based coating preparation, and in particular to a method for preparing a superhard and tough self-lubricating TiAlSiCN coating. Background Art
[0002] A fuel cell is a device that converts chemical energy into electrical energy, and has the advantages of high efficiency, low pollution and zero emissions. Among them, metal bipolar plates, as one of the main components of fuel cells, directly affect the performance and service life of fuel cells. When using hydrogen-containing gases, such as acetylene gas and methane, reactive sputtering to prepare carbon-based compounds will leave residual hydrogen, which will cause the coating to crack, fall off and fail during use, seriously affecting the life of the metal bipolar plates.
[0003] Magnetron sputtering is a vacuum coating technology that introduces a magnetic field on the target cathode surface and uses the magnetic field to constrain charged particles to increase the plasma density and increase the sputtering rate, achieving high-speed, low-temperature, and low-damage sputtering. It has the advantages of simple equipment, easy control, large coating area, and strong adhesion. At present, magnetron sputtering has been widely used in the preparation of surface coatings for fuel cell metal bipolar plates.
[0004] In order to improve the performance and service life of fuel cells, it is necessary to prepare a hydrogen-free carbon-based coating to improve the conductivity and corrosion resistance of metal bipolar plates, while reducing the hydrogen-carbon content of the coating to improve the efficiency and stability of fuel cells. Therefore, a method for preparing a superhard and tough self-lubricating TiAlSiCN coating is needed. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a superhard and tough self-lubricating TiAlSiCN coating.
[0006] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0007] The present invention adopts Ti70Al20Si10, Ti or Ti50Al50, C targets to prepare a smooth and dense TiAlSiCN nanocomposite coating on a tungsten steel alloy, stainless steel, copper alloy and high-speed steel substrate at high speed, comprising the following steps:
[0008] 1) Cleaning of substrate: Place the experimental substrate in a container of anhydrous alcohol or acetone, clean it with an ultrasonic cleaning instrument for 15-20 minutes, take it out and blow dry the substrate with compressed air, and set it aside for use;
[0009] 2) Substrate installation: Open the vacuum chamber, place the substrate on the sample platform, close the door and evacuate the chamber until the vacuum degree is lower than 5*10 -3 Pa;
[0010] 3) Ion cleaning: Use a pulsed DC power supply to connect to the substrate, set the pulse parameters: -500V, 100KHz, 1μs, gas pressure 0.3-2Pa, argon flow rate 100-130sccm, and clean the sample for 30 minutes;
[0011] 4) Preparation of Ti or TiAl metal bonding layer: Start high-power pulsed magnetron sputtering, set micro-pulse parameters 2-40s, average power 2-10kW, gas pressure 0.3-2Pa, argon flow 100-130sccm, bias -100--300V, high-energy bombardment of the substrate for 1-5 minutes, then reduce the bias to -60--100V to prepare a 300-500nm Ti or TiAl metal bonding layer;
[0012] 5) Preparation of TiAlSiN nanocomposite coating: connect a high-power pulsed magnetron sputtering device to a Ti70Al20Si10 target material, start high-power pulsed magnetron sputtering, set micro-pulse parameters of 2-40s, average power of 2-10kW, gas pressure of 0.8-2Pa, argon flow rate of 100-130sccm, bias voltage of -60--150V, and time of 20-60 minutes to prepare a TiAlSiN nanocomposite coating;
[0013] 6) Preparation of ultra-hard and tough self-lubricating TiAlSiCN coating: Select a target material combination, connect a high-power pulse power supply or a deep oscillation power supply in sequence to ensure sufficient ionization rate, and connect other targets to a pulsed DC power supply; set the high-power pulse power supply parameters, micro-pulse parameters: 6s / 30s, average power: 6-10kW, pulsed DC power supply parameters 100kHz, 0.4-8kW, gas pressure 0.6-2Pa, argon 80-160sccm and nitrogen flow 20-100sccm, bias -60~-300V, preparation process time 60-120 minutes, and take samples 30-60 minutes after the coating preparation is completed;
[0014] Furthermore, the TiAlSiCN nanocomposite coating has a thickness of 2-10 μm, a nanohardness of 48.3 GPa, and a H / E* greater than 0.16. 3 / E* 2 Greater than 0.32, Rockwell indentation bonding strength greater than HF1, elastic recovery greater than 60%, fracture toughness K IC Greater than 3MPa·m 1 / 2 .
[0015] Furthermore, the flow rates of argon and nitrogen are 80-160 sccm and 20-100 sccm, respectively.
[0016] Furthermore, the rotating speed of the turret is 1-3 rpm, and the deposition rate is 50-500 nm / min.
[0017] Furthermore, the target material combination method specifically includes:
[0018] 1) 1 TiAlSi, 2 Ti and 1 C target;
[0019] 2) 1 TiAlSi, 1 Ti, 1 TiAl and 1 C target;
[0020] 3) 1 TiSi, 1 Ti, 1 TiAl and 1 C target;
[0021] 4) 1 Si, 1 Ti, 1 TiAl and 1 C target;
[0022] 5) 2 TiAlSi, 1 TiAl and 1 C targets.
[0023] Furthermore, the ultra-hard and tough self-lubricating TiAlSiCN coating comprises a metal injection and bonding layer, a nitride gradient layer and a TiAlSiCN coating; the metal injection and bonding layer is a Ti or TiAl metal bonding layer; the nitride gradient layer can be a TiN, TiAlN and TiAlSiN layer; the thickness of the metal bonding layer is 0.3-1.0 μm, and the thickness of the nitride gradient layer is 0.3-0.5 μm.
[0024] Furthermore, the device for preparing the ultra-hard and tough self-lubricating TiAlSiCN coating includes a reaction chamber, and the reaction chamber is provided with a vacuum control system and a gas path control system. It is characterized in that the process chamber is provided with the four-target unbalanced magnetron sputtering system, and the four-target closed-field unbalanced magnetron sputtering system includes a cylindrical vacuum chamber, and the cylindrical vacuum chamber is a columnar ion source composed of two pairs of cathodes and target materials, the target material is provided on the cathode, and the two pairs of the cylindrical target materials are cross-arranged to form a closed magnetic field loop.
[0025] Furthermore, the four-target closed-field unbalanced magnetron sputtering system and the pulsed magnetron sputtering power supply are coupled into a plasma source, and a vacuum control system and a gas path control system are controlled by a computer to adjust the working gas pressure, gas flow and pulsed power supply parameters.
[0026] The beneficial effects of the present invention are:
[0027] The present invention is a method and system for preparing a super-hard and tough self-lubricating TiAlSiCN coating. Compared with the prior art, the present invention has the following technical effects:
[0028] This method can accurately control the performance of the coating by adjusting the parameters of the micro-pulse, has a fast deposition rate, is easy to operate, and has low cost. It meets the high performance, long life, and low cost design requirements of hydrogen fuel cell bipolar plates, and uses flammable and explosive acetylene gas, which is safer and more reliable. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic structural diagram of a device for preparing a superhard and tough self-lubricating TiAlSiCN coating according to the present invention;
[0030] Figure 2 A schematic diagram of a Vickers indentation photograph of a super-hard and tough self-lubricating TiAlSiCN coating prepared on a 316L stainless steel substrate according to the present invention; DETAILED DESCRIPTION
[0031] The present invention is further described below with specific examples. The illustrative examples and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0032] The method for preparing the superhard and tough self-lubricating TiAlSiCN coating of the present invention comprises the following steps:
[0033] like Figure 1 As shown, the present invention adopts Ti70Al20Si10, Ti or Ti50Al50, C targets to prepare a smooth and dense TiAlSiCN nanocomposite coating on a tungsten steel alloy, stainless steel, copper alloy and high-speed steel substrate at high speed, comprising the following steps:
[0034] 1) Cleaning of substrate: Place the experimental substrate in a container of anhydrous alcohol or acetone, clean it with an ultrasonic cleaning instrument for 15-20 minutes, take it out and blow dry the substrate with compressed air, and set it aside for use;
[0035] 2) Substrate installation: Open the vacuum chamber, place the substrate on the sample platform, close the door and evacuate the chamber until the vacuum degree is lower than 5*10 -3 Pa;
[0036] 3) Ion cleaning: Use a pulsed DC power supply to connect to the substrate, set the pulse parameters: -500V, 100KHz, 1μs, gas pressure 0.3-2Pa, argon flow rate 100-130sccm, and clean the sample for 30 minutes;
[0037] 4) Preparation of Ti or TiAl metal bonding layer: Start high-power pulsed magnetron sputtering, set micro-pulse parameters 2-40s, average power 2-10kW, gas pressure 0.3-2Pa, argon flow 100-130sccm, bias -100--300V, high-energy bombardment of the substrate for 1-5 minutes, then reduce the bias to -60--100V to prepare a 300-500nm Ti or TiAl metal bonding layer;
[0038] 5) Preparation of TiAlSiN nanocomposite coating: connect a high-power pulsed magnetron sputtering device to a Ti70Al20Si10 target material, start high-power pulsed magnetron sputtering, set micro-pulse parameters of 2-40s, average power of 2-10kW, gas pressure of 0.8-2Pa, argon flow rate of 100-130sccm, bias voltage of -60--150V, and time of 20-60 minutes to prepare a TiAlSiN nanocomposite coating;
[0039] 6) Preparation of ultra-hard and tough self-lubricating TiAlSiCN coating: Select the target material combination, connect the high-power pulse power supply or deep oscillation power supply in sequence to ensure sufficient ionization rate, and connect the other targets to the pulse DC power supply; set the high-power pulse power supply parameters, micro-pulse parameters: 6s / 30s, average power: 6-10kW, pulse DC power supply parameters 100kHz, 0.4-8kW, gas pressure 0.6-2Pa, argon and nitrogen flow 100-130
[0040] sccm, bias voltage -60--300V, preparation process time 60-120 minutes, sample is taken 30-60 minutes after coating preparation is completed;
[0041] In this embodiment, the TiAlSiCN nanocomposite coating has a thickness of 2-10 μm, a nanohardness of 48.3 GPa, and a H / E* greater than 0.16. 3 / E* 2 Greater than 0.32, Rockwell indentation bonding strength greater than HF1, elastic recovery greater than 60%, fracture toughness K IC Greater than 3MPa·m 1 / 2 .
[0042] In this embodiment, the flow rates of argon and nitrogen are 80-160 sccm and 20-100 sccm, respectively.
[0043] In this embodiment, the rotating speed of the rotary rack is 1-3 rpm, and the deposition rate is 50-500 nm / min.
[0044] In this implementation example, the target material combination method specifically includes:
[0045] 1) 1 TiAlSi, 2 Ti and 1 C target;
[0046] 2) 1 TiAlSi, 1 Ti, 1 TiAl and 1 C target;
[0047] 3) 1 TiSi, 1 Ti, 1 TiAl and 1 C target;
[0048] 4) 1 Si, 1 Ti, 1 TiAl and 1 C target;
[0049] 5) 2 TiAlSi, 1 TiAl and 1 C targets.
[0050] In this embodiment, the ultra-hard and tough self-lubricating TiAlSiCN coating includes a metal injection and bonding layer, a nitride gradient layer and a TiAlSiCN coating; the metal injection and bonding layer is a Ti or TiAl metal bonding layer; the nitride gradient layer can be a TiN, TiAlN and TiAlSiN layer; the thickness of the metal bonding layer is 0.3-1.0 μm, and the thickness of the nitride gradient layer is 0.3-0.5 μm.
[0051] In this embodiment, a superhard and tough self-lubricating TiAlSiCN coating preparation device includes a reaction chamber, on which a vacuum control system and a gas path control system are arranged, and is characterized in that the reaction chamber includes a sample loading chamber, a prefabrication chamber, a process chamber and a sample output chamber, the outlet end of the sample loading chamber is connected to the inlet end of the prefabrication chamber, the outlet end of the prefabrication chamber is connected to the inlet end of the process chamber, the outlet end of the process chamber is connected to the sample output chamber, the process chamber is provided with the four-target unbalanced magnetron sputtering system, the four-target closed-field unbalanced magnetron sputtering system includes a cylindrical vacuum chamber, the cylindrical vacuum chamber is a columnar ion source composed of two pairs of cathodes and target materials, the target material is arranged on the cathode, and the two pairs of the columnar target materials are cross-arranged to form a closed magnetic field loop.
[0052] In this embodiment, the four-target closed-field unbalanced magnetron sputtering system and the pulsed magnetron sputtering power supply are coupled into a plasma source, and a vacuum control system and a gas control system are controlled by a computer to adjust the working gas pressure, gas flow and pulsed power supply parameters.
[0053] Preparation of tungsten steel tool coating: The cleaned tool sample is mounted on the sample table, and the optimal parameters are repeated to prepare the TiAlSiCN nanocomposite coating.
[0054] Mechanical properties testing: Nanohardness, effective Young's modulus and elastic recovery are tested by nanoindentation and H / E* and H are calculated. 3 / E* 2 The bonding strength level is evaluated by indentation using a Rockwell hardness tester.
[0055] Dry wear performance test: Use a wear performance tester to test the cutting performance of coated tools.
[0056] Experimental data:
[0057] Figure 2 Vickers indentation of the ultra-hard and tough self-lubricating TiAlSiCN coating prepared on 316L stainless steel substrate.
[0058] No cracks were found in the 10g, 25g, and 50g indentations.
[0059] Table 1: Mechanical and tribological properties of the coatings
[0060]
[0061] Table 2 Comparison of coating performance parameters
[0062] Tool coating type Friction coefficient Cutting length Tool integrity DLC 0.05 2000m rupture TiAlSiN 0.21 2000m rupture TiAlSiCN 0.08 2000m Minor wear
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a superhard and tough self-lubricating TiAlSiCN coating. It is characterized in that The Ti70Al20Si10, Ti or Ti50Al50, C targets are used to prepare a smooth and dense TiAlSiCN nanocomposite coating on a tungsten steel alloy, stainless steel, copper alloy and high-speed steel substrate at high speed, including the following steps: 1) Cleaning of substrate: Place the experimental substrate in a container of anhydrous alcohol or acetone, clean it with an ultrasonic cleaning instrument for 15-20 minutes, take it out and blow dry the substrate with compressed air, and set it aside for use; 2) Substrate installation: Open the vacuum chamber, place the substrate on the sample platform, close the door and evacuate the chamber until the vacuum degree is lower than 5*10 - 3 Pa; 3) Ion cleaning: Use a pulsed DC power supply to connect to the substrate and set the pulse parameters: -500V, 100KHz, 1μs, Gas pressure 0.3-2Pa, argon flow rate 100-130sccm, clean the sample for 30 minutes; 4) Preparation of Ti or TiAl metal bonding layer: Start high-power pulsed magnetron sputtering, set micro-pulse parameters 2-40s, average power 2-10kW, gas pressure 0.3-2Pa, argon flow 100-130sccm, bias -100--300V, high-energy bombardment of the substrate for 1-5 minutes, then reduce the bias to -60--100V to prepare a 300-500nm Ti or TiAl metal bonding layer; 5) Preparation of TiAlSiN nanocomposite coating: high power pulsed magnetron sputtering connected Ti 70Al 20Si 10 target, Start high-power pulsed magnetron sputtering, set micro-pulse parameters to 2-40s, average power to 2-10kW, gas pressure to 0.8-2Pa, argon flow rate to 100-130sccm, bias voltage to -60--150V, and time to 20-60 minutes to prepare TiAlSiN nanocomposite coating; 6) Preparation of ultra-hard and tough self-lubricating TiAlSiCN coating: Select a target material combination, connect a high-power pulse power supply or a deep oscillation power supply in sequence to ensure sufficient ionization rate, and connect other targets to a pulsed DC power supply; set the high-power pulse power supply parameters, micro-pulse parameters: 6s / 30s, average power: 6-10kW, pulsed DC power supply parameters 100kHz, 0.4-8kW, gas pressure 0.6-2Pa, argon 80-160sccm and nitrogen flow 20-100sccm, bias -60~-300V, preparation process time 60-120 minutes, and take samples 30-60 minutes after the coating preparation is completed; 2. A method for preparing a superhard and tough self-lubricating TiAlSiCN coating according to claim 1, It is characterized in that TiAlSiCN nanocomposite coating thickness 2-10μm, nano hardness 48.3GPa, H / E* greater than 0.16, H 3 / E* 2 Greater than 0.32, Rockwell indentation bonding strength greater than HF1, elastic recovery greater than 60%, fracture toughness K IC Greater than 3MPa·m 1 / 2 .
3. The method for preparing the superhard and tough self-lubricating TiAlSiCN coating according to claim 1, It is characterized in that The flow rates of argon and nitrogen are 80-160 sccm and 20-100 sccm, respectively.
4. A method for preparing a superhard and tough self-lubricating TiAlSiCN coating according to claim 1, It is characterized in that The turret rotation speed was 1-3 rpm and the deposition rate was 50-500 nm / min.
5. A method for preparing a superhard and tough self-lubricating TiAlSiCN coating according to claim 1, It is characterized in that In step 6, the target material combination method specifically includes: 1) 1 TiAlSi, 2 Ti and 1 C target; 2) 1 TiAlSi, 1 Ti, 1 TiAl and 1 C target; 3) 1 TiSi, 1 Ti, 1 TiAl and 1 C target; 4) 1 Si, 1 Ti, 1 TiAl and 1 C target; 5) 2 TiAlSi, 1 TiAl and 1 C targets.
6. A method for preparing a superhard and tough self-lubricating TiAlSiCN coating according to claim 1, It is characterized in that The ultra-hard and tough self-lubricating TiAlSiCN coating comprises a metal injection and bonding layer, a nitride gradient layer and a TiAlSiCN coating; the metal injection and bonding layer is a Ti or TiAl metal bonding layer; the nitride gradient layer can be a TiN, TiAlN and TiAlSiN layer; the thickness of the metal bonding layer is 0.3-1.0 μm, and the thickness of the nitride gradient layer is 0.3-0.5 μm.
7. An apparatus for preparing a superhard and tough self-lubricating TiAlSiCN coating, for executing the method according to claims 1 to 6, comprising a reaction chamber, wherein the reaction chamber is provided with a vacuum control system and a gas circuit control system, It is characterized in that The four-target unbalanced magnetron sputtering system is arranged in the process chamber. The four-target closed-field unbalanced magnetron sputtering system includes a cylindrical vacuum chamber. The cylindrical vacuum chamber is a columnar ion source composed of two pairs of cathodes and target materials. The target materials are arranged on the cathodes, and two pairs of the columnar targets are cross-arranged to form a closed magnetic field loop.
8. The device for preparing the superhard and tough self-lubricating TiAlSiCN coating according to claim 7, It is characterized in that The four-target closed-field unbalanced magnetron sputtering system and the pulsed magnetron sputtering power supply are coupled into a plasma source, and a vacuum control system and a gas path control system are controlled by a computer to adjust the working gas pressure, gas flow and pulsed power supply parameters.
